Effectiveness of teacher training conducted at Chitwan Medical College, Bharatpur, Nepal - Dhungana, G P; Piryani, R M; Chapagain, M L; Neupane, M (Journal of Chitwan Medical College, 2015)
Teaching and learning are equally important for the teacher. For teaching to be effective, whereby participants learn better, training of teachers is imperative. Teacher’s training is one of the important aspects of faculty development at Chitwan Medical College (CMC) and this study was done to assess the effectiveness of the teachers’ training pre test, post test experimental group design. In pre test, only 5.6% of the participants had adequate knowledge whereas after teacher’s training, 27.7 % had adequate knowledge. The mean (±SD) knowledge score before and after the intervention was 26.7±5.6 and 33.6 ± 5.6 respectively. The percent change in knowledge after intervention was 25.8 was statistically significant p value <0.001 .Which suggesting that the teachers’ training was an effective intervention.